ANALISIS FAKTOR YANG MEMPENGARUHI PRODUKSI BATU BATA DI KABUPATEN TABANAN - Triyana, I Komang Yoga; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 12 (2024): Vol.13.No.12. DESEMBER 2024 [831-914]DO - 10.24843/EEP.2024.v13.i12.p04, 2025)
One of the highest processing industries in Tabanan Regency is the red brick industry. Of all sectors that contribute to per capita income, the processing industry has experienced an increase. The aim to analyze the indirect influence of labor and capital on the income of brick industry entrepreneurs through brick production in Tabanan Regency. This research uses a quantitative and associative approach. The population used by researchers in this research was 442 brick industry entrepreneurs in Tabanan Regency with a total sample of 82 respondents. The approach in this research is quantitative statistics and analysis techniques using multiple regression analysis. Based on the results of data analysis, it shows that Labor and Capital directly have a positive and significant influence on Brick Production in Tabanan Regency, Labor, Capital and Production directly have a positive and significant influence on the Income of Brick Industry Entrepreneurs in Tabanan Regency and Labor and Capital directly. does not directly affect the income of brick industry entrepreneurs through brick production in Tabanan Regency. Keywords: Labor, Capital, Production, Income